Characterization of the novel HLA‐DQA1*01:80 allele by next generation sequencing. (13th September 2021) - Jacob, Valentine; Farce, Fabienne; Kaveri, Rangolie; Desoutter, Judith; Guillaume, Nicolas
Abstract : HLA‐DQA1*01:80 differs from HLA‐DQA1*01:04:01 by one nucleotide substitution in codon −18 in exon 1.